2017
DOI: 10.1016/j.neuron.2017.04.041
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII Autophosphorylation Is Necessary for Optimal Integration of Ca 2+ Signals during LTP Induction, but Not Maintenance

Abstract: SUMMARY CaMKII plays a critical role in decoding calcium (Ca2+) signals to initiate long-lasting synaptic plasticity. However, the properties of CaMKII that mediate Ca2+ signals in spines remain elusive. Here, we measured CaMKII activity in spines using fast-framing two-photon fluorescence lifetime imaging. Following each pulse during repetitive Ca2+ elevations, CaMKII activity increased in a stepwise manner. Thr286 phosphorylation slows the decay of CaMKII and thus, lowers the frequency required to induce spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
223
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(263 citation statements)
references
References 43 publications
17
223
0
Order By: Relevance
“…Modest relearning occurred over the three subsequent trials (trials 14-16 in Fig.4C), perhaps due to non-transfected cells (see Methods for quantification and (Moser and Moser, 1998; Rumpel et al, 2005) for evidence that behavioral effects do not require that all neurons are affected). According to the model of (Chang et al, 2017), CaMKII has no role in memory maintenance; because some other process encodes memory, that information should be retrievable despite the action of CaMKII*. The results in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Modest relearning occurred over the three subsequent trials (trials 14-16 in Fig.4C), perhaps due to non-transfected cells (see Methods for quantification and (Moser and Moser, 1998; Rumpel et al, 2005) for evidence that behavioral effects do not require that all neurons are affected). According to the model of (Chang et al, 2017), CaMKII has no role in memory maintenance; because some other process encodes memory, that information should be retrievable despite the action of CaMKII*. The results in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Other work using the same mutation (Villers et al, 2014) measured LTP over longer periods and found that normal LTP was not maintained but, rather, was replaced by a form of potentiation that does not have synapse specificity or NMDAR dependence. In summary, the model of (Chang et al, 2017; Murakoshi et al, 2017) leaves a large number of experimental results demonstrating long-lasting changes in CaMKII unexplained (Ahmed and Frey, 2005; Fukunaga et al, 1993; Lengyel et al, 2004; Otmakhov et al, 2004) and is inconsistent with results showing that manipulations of CaMKII during the maintenance period can affect LTP (Barcomb et al, 2016; Sanhueza et al, 2011) and behavior (Figs. 3,4).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Fluorescence lifetime images were collected by 128 x 128 pixels acquired at 2 ms/line and averaged over 24 frames. The fluorescence lifetime of mEGFP was measured by curve fitting as previously described (65). Unpaired Student's t-tests (two-tailed, 95% confidence) compared RPM-1::mEGFP alone with RPM-1::mEGFP + mCherry::FSN-1, or with RPM-1::mEGFP + mCherry expressed in the mechanosensory neurons.…”
Section: Two Photon Flimmentioning
confidence: 99%